Ameliorative effect of caffeic acid phenethyl ester on histopathological and biochemical changes induced by cigarette smoke in rat kidney - Pekmez, Hidir; Ogeturk, Murat; Ozyurt, Huseyin; Sonmez, Mehmet Fatih; Colakoglu, Neriman; Kus, Ilter (Sage Publications Inc, 2010)
It was aimed to investigate the histopathological and biochemical changes in kidney tissues of rats exposed to cigarette smoke and possible protective effects of caffeic acid phenethyl ester (CAPE) on these changes. Twenty one male Wistar albino rats were divided into three equal groups. Animals in group I were used as control. Rats in group II were exposed to cigarette smoke and rats in group III were exposed to cigarette smoke and daily administration of CAPE. At the end of the 60-day experimental period, all the animals were sacrificed by decapitation. The serum samples obtained from the animals were studied for uric acid, creatinine and blood urine nitrogen (BUN) levels. Following routine histological procedures, kidney tissue specimens were examined under a light microscope. In addition, dismutase (SOD) and glutathione peroxidase (GSH-Px) enzyme activities and malondialdehyde (MDA) and nitric oxide (NO) contents were determined spectrophotometrically in tissue samples. It was found that serum uric acid and BUN levels of the rats exposed to cigarette smoke alone were elevated, although serum creatinine levels did not significantly change. Furthermore, renal SOD, GSH-Px, NO and MDA levels were significantly increased. These increases in serum BUN, and renal SOD, GSH-Px, NO and MDA levels were significantly inhibited by CAPE treatment. In light microscopic observations of tissues from rats exposed to smoke, mesangial cell proliferation in the renal corpuscles, dilatation and congestion in the peritubular capillaries and degenerative alterations in the proximal tubules were noted. There were also atrophic renal corpuscles. However, these histopathological changes were partially disappeared in the rats exposed to cigarette smoke plus CAPE. The present findings indicate that cigarette smoke causes impairment in renal structure and function, which can be prevented by CAPE administration.
Keywords: cigarette; caffeic acid phenethyl ester; kidney; histopathology; biochemistry